Learning MCollective parallel server management in Puppet and Chef - Rhett, Jo (O'Reilly Media, 2014)
Ideal for system administrators and operations or DevOps engineers at any level, this hands-on guide teaches you how to build and test a real installation of MCollective servers and clients in your environment.